Comparison between Coherent and Noncoherent Receivers for UWB Communications - Benedetto Sergio; Durisi Giuseppe (EURASIP Journal on Advances in Signal Processing, 2005)
We present a comparison between coherent and noncoherent UWB receivers, under a realistic propagation environment, that takes into account also the effect of path-dependent pulse distortion. As far as coherent receivers are concerned, both maximal ratio combining (MRC) and equal gain combining (EGC) techniques are analyzed, considering a limited number of estimated paths. Furthermore, two classical noncoherent schemes, a differential detector, and a transmitted-reference receiver, together with two iterative solutions, recently proposed in the literature, are considered. Finally, we extend the multisymbol approach to the UWB case and we propose a decision-feedback receiver that reduces the complexity of the previous strategy, thus still maintaining good performance. While traditional noncoherent receivers exhibit performance loss, if compared to coherent detectors, the iterative and the decision-feedback ones are able to guarantee error probability close to the one obtained employing an ideal RAKE, without requiring channel estimation, in the presence of static indoor channel and limited multiuser interference.